(untitled) - Konieczka, Piotr (Boca Raton, 2009)
Clearly written and logically organized, this book delineates the concepts of practical QA/QC, taking a generic approach that can be applied to any field of analysis. Using an approach grounded in hands-on experience, the book begins with the theory behind quality control systems and then moves on to discuss examples of tools such as validation parameter measurements, the use of statistical tests, counting the margin of error, and estimating uncertainty. The authors draw on their experience in uncertainty estimation, traceability, reference materials, statistics, proficiency tests, and method validation to provide practical guidance on each step of the process.
Keywords: Chemical laboratories,Chemistry, analytic; Quality control,Qualitative